Primary Pyomyositis Mimicking Transient Synovitis of the Hip in a Child: A Case Report - Salih KAVUKÇU,; Can KOŞAY,; Handan ÇAKMAKÇI,; Yeşim ÖZTÜRK,; Özden ANAL, (Archives of Rheumatology, 2012)
Pyomyositis, which is an uncommon pyogenic infection of skeletal muscle, is a rare, but potentially serious disease in children. Pyomyositis can be easily confused with more benign conditions, thus serious complications including compartment syndrome, contiguous osteomyelitis, extension into and destruction of an adjacent joint, sepsis and death may occur. Early diagnosis established with magnetic resonance imaging or computed tomography, prompt drainage of the abscess, microbiological studies and appropriate intravenous antibiotic treatment prevent complications and provide successful management of pyomyositis in children. In this paper, we present a case with gluteal pyomyositis who was initially misdiagnosed as transient synovitis and suffered from contiguous osteomyelitis due to delay in diagnosis.